A Higher Estradiol Rise After Dual Trigger in Progestin-Primed Ovarian Stimulation Is Associated With a Lower Oocyte and Mature Oocyte Yield in Normal Responders - Huang, Jialyu (Front Endocrinol (Lausanne), 2019)
Background: Prior studies have shown that patients with a >10% estradiol (E(2)) rise after trigger had more oocytes retrieved than plateauing or decreasing E(2) responders. However, multiple follicles develop at different stages of maturation during controlled ovarian stimulation (COS) and may exhibit different responses to trigger. The association between the magnitude of E(2) increase and oocyte retrieval outcomes is still unclear. Methods: This was a retrospective cohort study of 2,898 women undergoing their first COS cycles with normal response from January 2014 to December 2017 at a tertiary-care academic medical center. Patients were categorized into five groups according to the percentage increase in E(2) levels before and after dual trigger: <10.0%, 10.0–19.9%, 20.0–29.9%, 30.0–39.9%, and ≥40.0%. Univariable and multivariable linear regression analysis were performed to explore the association between E(2) increase and oocyte/mature oocyte yield, while logistic regression was used to assess its effect on low oocyte/mature oocyte yield (<10th percentile). Results: The post-trigger E(2) increase was negatively associated with both oocyte yield (P-trend < 0.001, adjusted P-trend = 0.033) and mature oocyte yield (P-trend < 0.001, adjusted P-trend = 0.002). Compared with a <10.0% E(2) increase after trigger, patients with a ≥40.0% rise had fewer mature oocyte yield [adjusted mean absolute difference [MD] = −5.2, 95% confidence interval [CI]: −8.2–−1.8] and higher risk of low mature oocyte yield (adjusted odds ratio [OR] = 1.64, 95% CI: 1.04–2.60), whereas no statistical significance was found in oocyte yield (adjusted MD = −2.7, 95% CI: −6.1–0.8) and low oocyte yield (adjusted OR = 1.48, 95% CI: 0.96–2.28). In addition, the rates of implantation, positive pregnancy test, clinical pregnancy, ongoing pregnancy, pregnancy loss, and live birth were comparable among the 1,942 frozen embryo transfer cycles with embryos originating from different groups of E(2) increase (all P > 0.05). Conclusions: A higher E(2) rise after dual trigger is independently associated with a lower oocyte and mature oocyte yield in normal responders. Further studies are needed to explore the efficacy of individualized time interval from trigger to oocyte retrieval based on the magnitude of E(2) increase after trigger.